A review on shrinkage-reducing methods and mechanisms of alkali-activated/geopolymer systems: Effects of chemical additives. (15th May 2022) - Zhang, Bai; Zhu, Hong; Feng, Pan; Zhang, Pu
Abstract: Alkali-activated binders or geopolymers are identified as an ideal substitute for ordinary Portland cement (OPC) binders because of their outstanding mechanical characteristics and durability. However, the high-magnitude shrinkage for alkali-activated composites induces uneven deformation across the material and further triggers the formation of harmful cracks, which creates ways for various aggressive substances to permeate the composites, severely reducing the load capacity and threatening the durability of concrete structures. Recently, relevant researchers have reported adding chemical additives is an effective way in alleviating the shrinkage for alkali-activated or geopolymer systems. However, to date, only limited information summarizing and classifying these chemical additives and their shrinkage-reducing mechanisms is available. Therefore, this paper presents a well-documented literature review on the shrinkage characteristics for alkali-activated or geopolymer composites, and systematically summarizes chemical additive types and their shrinkage-reducing mechanisms. The frequently-used chemical additives in alkali-activated or geopolymer systems can be divided into four types: expansive agents (EAs), shrinkage-reducing admixtures (SRAs), superabsorbent polymers (SAPs), and nano-particles (NPs). Then, the influences of these chemical additives on the mechanical behavior and shrinkage for geopolymer or alkali-activated systems were compared and discussed. It was found that the inclusion of SAPs achieved the best shrinkage-mitigating effect, followed by SRAs, EAs, and NPs, respectively. There were about 30%, 45%, and 55% declines in the shrinkage of alkali-activated or geopolymer systems when 3% NPs, EAs, and SRAs were added. Whereas, a reduction of about 70% can be observed by incorporating only 0.3% SAPs. Additionally, it is concluded that the shrinkage reduction mechanisms achieved by the application of these chemical additives are primarily ascribed to densifying the pore structures, reducing the total porosity as well as the proportion of mesopores, coarsening the pore structures, and promoting the generation of crystalline phases (i.e., calcium hydroxide, AFt, and AFm). Highlights: The shrinkage-reducing methods and mechanisms and of alkali-activated/geopolymer systems were discussed. Effects of various chemical additives on shrinkage characteristics of alkali-activated systems were compared. Mechanisms of shrinkage reduction depend mainly on the adjusted reaction products and optimized pore structure.